An isotope label method for empirical detection of carbonic anhydrase in the calcification pathway of the coccolithophore Emiliania huxleyi. (1st January 2021) - Zhang, Hongrui; Blanco-Ameijeiras, Sonia; Hopkinson, Brian M.; Bernasconi, Stefano M.; Mejia, Luz Maria; Liu, Chuanlian; Stoll, Heather
Abstract: Coccolithophores are a group of phytoplankton widely distributed in the ocean, which secrete extracellular calcite plates termed coccoliths. Coccoliths have been increasingly employed as an archive for geochemical, ecological and paleoclimate studies in recent years. A robust application of coccolith-based geochemical proxies relies on understanding the carbon acquisition strategies and the pathways of carbon supply for calcification. Carbonic anhydrase (CA) plays important roles in the carbon concentrating mechanism s of aquatic algae and potentially also in calcification. However, it is difficult to independently assess the role of CA in carbon supply for photosynthesis versus calcification. To fill this gap, we explored a new method to detect the CA activity inside coccolithophore. To achieve this, coccolithophores were cultured with oxygen and carbon isotope labeled dissolved inorganic carbon (DIC). By exploiting the different behavior of oxygen and carbon isotopes with (sea)water, this double label method can elucidate the significance of CA activity in the calcification pathway. Application of this method to Emiliania huxleyi shows that CA is present in the calcification pathway, and that there is no significant difference in the CA activity between a high and low CO2 treatment. However, under low CO2 treatment E. huxleyi enhanced the bicarbonate pumping rate on both cell and chloroplast membranes. This novel method could be performed on other species of coccolithophores in the future and have a potential to extend our knowledge on coccolith oxygen isotope vital effects.